In vivo morphometry of menisci of the knee in South Indians: A preliminary study - K.V.N. Dhananjaya (Biomedical Journal, 2014)
Background: Since the in vivo morphometric data on the menisci of the knee joint of Indian subjects are scarce, we hereby studied the width and thickness of the menisci using Magnetic Resonance Imaging (MRI) to establish standard dimensions of the normal medial and lateral meniscus as an aid to orthopaedic surgery. Methods: Eighty menisci from 40 knee joints were analysed in each of three regions, the anterior horn, the mid body and the posterior horn. The thickness and width of the menisci were measured in sagittal and coronal T1-weighted and T2-weighted MRI images and analysed statistically. Results: The mean thickness of medial meniscus at the anterior horn, mid body, and posterior horn were 6.3 ± 1.1 mm, 5.2 ± 1.3 mm, and 6.9 ± 1.1 mm, respectively. The respective values for the lateral meniscus were 4.8 ± 0.7 mm, 6.4 ± 1.1 mm, and 7.0 ± 0.9 mm. The mean width of medial meniscus at the anterior horn, mid body, and posterior horn were 10.5 ± 1.2 mm, 7.8 ± 1 mm and 13.9 ± 0.9 mm, respectively. The widths of lateral meniscus at the same regions were 11.8 ± 1.4 mm, 8.6 ± 1.2 mm, and 12.0 ± 0.9 mm, respectively. The lateral meniscus was significantly wider than medial at the anterior horn and mid body (p = 0.00). In contrast, the posterior horn of medial meniscus was significantly wider than lateral meniscus. Both menisci were significantly wider at their posterior horn, followed by the anterior horn and were significantly narrower at their mid body. Conclusion: The present study provides new information on the meniscal thickness and width in South Indians that can be used in planning of orthopaedic and arthroscopic surgeries of the knee joint. However, the study needs to be analyzed with a large sample size for the better interpretation.